2020
DOI: 10.13005/bpj/2078
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Mobile Phone Use in The School Going Children in North Al Batinah Region of Oman: A Cross Sectional Study

Abstract: The use of mobile phones has become increasingly common among general population, but how much has it increased among the young school going population remains to be seen.Our objective was to investigate the prevalence of mobile phone use, during and after school hours, and its ownership in the primary and secondary section students in Oman.We surveyed 414 students in Cycle 1 and 1438 students in Cycle 2 in the city of Sohar, North Al Batinah region of Oman. Students completed a paper-based questionnaire about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…91% of students from secondary section whose average age was 14±2.16 years actively used mobile phones. 10 In our study out of 248 children 45 of them owned a mobile phone. No significant difference was noted in mobile phone usage across socio economic status, unlike the study by Byun who reported that more children belonging to lower socio economic position communities owned a mobile phone compared to those of higher socioeconomic position.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…91% of students from secondary section whose average age was 14±2.16 years actively used mobile phones. 10 In our study out of 248 children 45 of them owned a mobile phone. No significant difference was noted in mobile phone usage across socio economic status, unlike the study by Byun who reported that more children belonging to lower socio economic position communities owned a mobile phone compared to those of higher socioeconomic position.…”
Section: Resultsmentioning
confidence: 94%
“…Not only in Oman but also all over the world the mobile phone ownership among children and also the duration of time utilized on internet has increased exponentially during the recent few years. 10 The excessive mobile phone usage by the parents in home environment influences the behavior of the children. More often than not the caregivers are engrossed by the mobile phone to such an extent that it hinders their responsiveness to the child.…”
Section: Resultsmentioning
confidence: 99%
“…The share of family circle with access to the Internet similarly increased from 18% in 2005 to 46% in 2015. [22,21]. Smartphones can process many data and information than other mobile phones, it includes many apps like sports, internet and social media access, messaging, video, multimedia and travel, about using them meant for communication.…”
Section: Smartphone Usagementioning
confidence: 99%